"This May Create a Zero-lingual State": Critical Examination of Language Ideologies in an English Learning Blog. (25th August 2018) - Song, Rayoung
Abstract : Given the importance of the blogosphere for autonomous language learning, many studies on computer-assisted language learning (CALL) have vigorously investigated the use of blogs in language learning. Noticeably lacking in these endeavors are investigations of language learners' social engagement with others in online spaces to define and negotiate their own meanings of language and language learning. To fill this gap, this study investigated the language ideologies disseminated in a Korean blog that has become a collaborative online English-learning community. Focusing on this blog owner's ideas and her followers' responses, I explored the language ideologies disseminated and negotiated in conversations on language learning and using. This is part of a larger virtual ethnographic study conducted over the past three years. I analyzed online posts and comments using Gee's situated meanings (2014). Findings suggest that the Korean bloggers subscribe to monolingual ideologies because they are acutely aware of the ideological contexts in Korea surrounding English and are critical about their own language learning and using practices. The current study asserts that the blogosphere can create opportunities for language learners to contest existing knowledge and voice their opinions on issues that matter to them as language learners and members of a society.